Propagation of Immigration Shocks through Firm-to-Firm Trade Networks - Yusuf Emre Akgündüz; Abdurrahman B. Aydemir; Seyit Mümin Cilasun; Murat Güray Kirdar (Institute of Labor Economics (IZA), 2024)
This paper investigates the degree to which immigration shock to a region propagates through supply chains. Using the unexpected arrival of Syrian refugees densely concentrated in border regions of Turkey, we estimate how firms throughout the country are affected in terms of their sales, employment, and wages. We also estimate the effect of the shock on interprovincial trade, focusing on trade volume and network formation. The results point to positive spillover effects of immigration for firms with pre-existing links to Syrian refugee-hosting regions through upstream and downstream linkages. We further find evidence for increased trade volume and network expansion through new trade linkages.
Keywords: D22; J61; L14; 330; immigration; propagation; firm-to-firm trade; employment; production networks